The water footprint of lithium extraction technologies: Insights from environmental impact reports in Argentina's salt flats - Walter Fernando Díaz Paz; Lucas Seghezzo; Ariela Griselda Salas Barboza; Melisa Escosteguy; Paula Valentina Arias-Alvarado; Eduardo Kruse; Marc Hufty; Martín Alejandro Iribarnegaray (Heliyon)
This study estimates water consumption in two lithium mines (Olaroz and Fénix) that use different extraction technologies in Argentina's salt flats. Based on Environmental Impact Reports (EIRs), we assess the water footprint (WF) and brine consumption (BC) in both mines. To the best of our knowledge, this study is the first to estimate WF and BC for lithium extraction and provides data to assess water consumption and better understand its implications for local ecosystems and communities. We also contextualize freshwater consumption in lithium extraction projects by estimating the blue water intensity (WIblue) and the population equivalent (PE), namely the number of local inhabitants that would consume an equivalent volume of water. Total WF was 51.0 and 135.5 m3/ton of lithium carbonate (Li2CO3) for Olaroz and Fénix, respectively. Per unit of product, WF was 2.7 times higher in Fénix but BC was higher in Olaroz. WIblue indicates that, while Fénix had a higher WFblue, its impact on local blue water availability is moderate due to greater local water availability. WFblue in Olaroz and Fénix was equivalent to the water consumption of 32,238 and 141,047 inhabitants of their nearest towns (Susques and Antofagasta de la Sierra, respectively, both with a current population of less than 2,100 inhabitants). Our findings underscore that the water consumption of lithium mining can have important impacts that vary significantly with geographic context. EIRs provide a useful basis for estimating WF and BC, though certain limitations and challenges persist, particularly regarding incomplete or insufficiently detailed data.